2018
DOI: 10.21638/spbu03.2018.104
|View full text |Cite
|
Sign up to set email alerts
|

The study of plant adaptation to oxygen deficiency in Saint Petersburg University

Abstract: The first studies on plant anaerobiosis started at the Department of Plant Physiology at St. Petersburg University in the beginning of the 20 th century, but interest in this subject became most intensive during the investigations of the ecological plant physiology group under the supervision of Prof. T. V. Chirkova. Their first step was focused on the mechanisms of transport of gases from the aerated aboveground part of the plant to the flooded root system. Further interest shifted towards clarifying the bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 31 publications
0
32
0
5
Order By: Relevance
“…The flooded environment, created during rice cultivation, provides anaerobic conditions that favor CH 4 production by methanogens [39]. A study concluded that anaerobic conditions affect glycolysis promoting ethanol and lactate production through ethanolic fermentation pathway [40]. In a study, it is mentioned about the toxicity of ethanol since it can diffuse out of the cell and results in the formation of acetaldehyde as a toxic intermediate [41].…”
Section: Submergence/floodingmentioning
confidence: 99%
“…The flooded environment, created during rice cultivation, provides anaerobic conditions that favor CH 4 production by methanogens [39]. A study concluded that anaerobic conditions affect glycolysis promoting ethanol and lactate production through ethanolic fermentation pathway [40]. In a study, it is mentioned about the toxicity of ethanol since it can diffuse out of the cell and results in the formation of acetaldehyde as a toxic intermediate [41].…”
Section: Submergence/floodingmentioning
confidence: 99%
“…Higher plants strongly depend on ambient oxygen concentration. The plant facilities to survive oxygen deprivation have been studied for decades [3][4][5][6][7]. Partial (hypoxia) or complete lack of oxygen (anoxia) characterizes both natural and agricultural ecosystems and has a serious economic impact [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The first one is based on a rapid shoot growth, hyponastic bending of leaves, formation of aerenchyma, initiation of adventitious roots, and alteration of leaf anatomy to improve the diffusion of gases, etc. [4][5][6]. This is a strategy to avoid oxygen deprivation by facilitating gas exchange between the submerged and aerated organs of plant.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations